Sealing material and its manufacturing method

JP7630472B2Active Publication Date: 2025-02-17MITSUBISHI CABLE INDUSTRIES LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022161774
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-10-06
Publication Date
2025-02-17
Estimated Expiration
2042-10-06

Smart Images

  • Figure 0007630472000001
    Figure 0007630472000001
  • Figure 0007630472000002
    Figure 0007630472000002
Patent Text Reader

Abstract

To provide a sealant that achieves excellent radical resistance.SOLUTION: A sealant is produced using an uncrosslinked rubber composition comprising a hydrogen-containing fluororubber, a heat crosslinking agent, and a radical resistance improver. The radical resistance improver consists only of Liquid A in a two-component material that comprises Liquids A and B, where Liquid A comprises a compound with a perfluoro skeleton comprising two or more alkenyl groups within the molecule, and Liquid B comprises a compound with a perfluoro skeleton comprising two or more alkenyl groups within the molecule and a crosslinking agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealing material and a method for producing the same. [Background technology]

[0002] Sealing materials formed from crosslinked rubber compositions of hydrogen-containing fluororubber are known. For example, Patent Document 1 discloses a sealing material formed from a crosslinked rubber composition obtained by crosslinking an uncrosslinked rubber composition containing a hydrogen-containing fluororubber, an organic peroxide, and a one-component material containing a perfluoro skeleton compound having two or more alkenyl groups in the molecule. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-52226 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a sealing material having excellent radical resistance. [Means for solving the problem]

[0005] The present invention provides an uncrosslinked rubber composition containing a hydrogen-containing fluororubber, a thermal crosslinking agent, and a radical resistance improver. A crosslinked rubber composition is formed. A sealing material, wherein the radical resistance improver contains a perfluoro skeleton compound having two or more alkenyl groups in the molecule. And does not contain crosslinking agents A two-component material having a liquid A and a liquid B containing a perfluoro skeleton compound having two or more alkenyl groups in the molecule and a crosslinking agent, the material being composed only of the liquid A. The uncrosslinked rubber composition contains only the A liquid of the two-component material, and does not contain the B liquid. .

[0006] The present invention relates to The method for producing a sealing material of the present invention comprises the steps of: A hydrogen-containing fluororubber; The above A thermal crosslinking agent; The aboveContains a radical resistance improver The above After preparing the uncrosslinked rubber composition, the uncrosslinked rubber composition is molded into an uncrosslinked molded article having a shape of a sealing material, and the uncrosslinked molded article is heated to crosslink the hydrogen-containing fluororubber with the thermal crosslinking agent, thereby obtaining a molded article. Effect of the Invention

[0007] According to the present invention, excellent radical resistance can be obtained by using only liquid A of a two-component material having liquid A containing a perfluoro skeleton compound having two or more alkenyl groups in its molecule and liquid B containing a perfluoro skeleton compound having two or more alkenyl groups in its molecule and a crosslinking agent as a radical resistance improver to be contained in an uncrosslinked rubber composition used for producing a sealing material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The embodiments will be described in detail below.

[0009] The sealing material according to the embodiment is manufactured using an uncrosslinked rubber composition containing a hydrogen-containing fluororubber, a thermal crosslinking agent, and a radical resistance improver. That is, this sealing material is formed of a crosslinked rubber composition in which an uncrosslinked molded body of the uncrosslinked rubber composition in the shape of a sealing material is heated to crosslink the hydrogen-containing fluororubber with a thermal crosslinking agent. The radical resistance improver is composed of only the former liquid A, which does not contain a crosslinking agent, out of a two-liquid material having a liquid A containing a perfluoro skeleton compound having two or more alkenyl groups in the molecule (hereinafter referred to as "compound X") and a liquid B containing compound X and a crosslinking agent.

[0010] According to the sealing material of this embodiment, excellent radical resistance can be obtained by using only the liquid A of a two-liquid type material having a liquid A containing compound X and a liquid B containing compound X and a crosslinking agent as a radical resistance improver contained in an uncrosslinked rubber composition used for producing the sealing material. Therefore, this sealing material can be suitably used in semiconductor process equipment that uses plasma, such as a semiconductor etching device or a plasma CVD device.

[0011] The hydrogen-containing fluororubber constitutes the rubber component of the matrix in the uncrosslinked rubber composition and the crosslinked rubber composition. Here, the "hydrogen-containing fluororubber" in the present application refers to a fluororubber containing carbon bonded to hydrogen in the main chain of the polymer.

[0012] Examples of hydrogen-containing fluororubbers include polymers of vinylidene fluoride (VDF) (PVDF), copolymers of vinylidene fluoride (VDF) and hexafluoropropylene (HFP), copolymers of vinylidene fluoride (VDF), hexafluoropropylene (HFP) and tetrafluoroethylene (TFE), copolymers of tetrafluoroethylene (TFE) and propylene (Pr) (FEP), copolymers of vinylidene fluoride (VDF), propylene (Pr) and tetrafluoroethylene (TFE), copolymers of ethylene (E) and tetrafluoroethylene (TFE) (ETFE), copolymers of ethylene (E), tetrafluoroethylene (TFE) and perfluoromethylvinyl ether (PMVE), copolymers of vinylidene fluoride (VDF), tetrafluoroethylene (TFE) and perfluoromethylvinyl ether (PMVE), copolymers of vinylidene fluoride (VDF) and perfluoromethylvinyl ether (PMVE), and the like. The hydrogen-containing fluororubber preferably contains one or more of these, and more preferably contains a vinylidene fluoride rubber (FKM) having vinylidene fluoride (VDF) as a monomer.

[0013] The thermal crosslinking agent crosslinks the hydrogen-containing fluororubber when heated to a predetermined temperature. Examples of the thermal crosslinking agent include peroxides, polyols, polyamines, triazines, etc. Among these, peroxides are preferred as the thermal crosslinking agent, from the viewpoint that it is not necessary to use an acid acceptor that causes particle generation in a plasma atmosphere.

[0014] Examples of the peroxide of the thermal crosslinking agent include 1,1-bis(t-butylperoxy)-3,5,5-trimethylcyclohexane, 2,5-dimethylhexane-2,5-dihydroperoxide, di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, α,α-bis(t-butylperoxy)-p-diisopropylbenzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)-hexyne-3, benzoyl peroxide, t-butylperoxybenzene, t-butylperoxymaleic acid, t-butylperoxyisopropyl carbonate, t-butylperoxybenzoate, etc. The peroxide of the thermal crosslinking agent preferably contains one or more of these, and more preferably contains 2,5-dimethyl-2,5-di(t-butylperoxy)hexane.

[0015] The content of the peroxide of the thermal crosslinking agent in the uncrosslinked rubber composition is preferably 0.5 parts by mass or more and 2.5 parts by mass or less, more preferably 0.5 parts by mass or more and 2.0 parts by mass or less, relative to 100 parts by mass of the hydrogen-containing fluororubber, from the viewpoints of sufficiently promoting crosslinking and obtaining good physical properties as a sealing material.

[0016] The radical resistance improver improves the radical resistance of the sealing material according to the embodiment. As described above, the radical resistance improver is composed of only the former A liquid, which does not contain a crosslinking agent, of the two-component material having an A liquid containing a compound X and a B liquid containing a compound X and a crosslinking agent. Examples of commercially available two-component materials include SIFEL3405A / B, SIFEL3505A / B, and SIFEL3705A / B of the SIFEL series manufactured by Shin-Etsu Chemical Co., Ltd.

[0017] Examples of the compound X contained in the A liquid constituting the radical resistance improver include compounds having a perfluoropolyether structure and compounds having a perfluoroalkylene structure. Examples of the alkenyl group include vinyl groups, allyl groups, butenyl groups, pentenyl groups, hexenyl groups, and heptenyl groups. Of these, the alkenyl group is preferably a vinyl group. The two or more alkenyl groups may be the same or different.

[0018] Examples of the crosslinking agent not contained in the solution A constituting the radical resistance improver include organohydrogenpolysiloxane that reacts with the alkenyl group of the compound X.

[0019] The solution A constituting the radical resistance improver may contain silica in addition to the compound X. From the viewpoint of obtaining excellent radical resistance, the content of silica in the solution A is preferably 25% by mass or less, more preferably 20% by mass or less, and further preferably 15% by mass or less. The solution A may further contain a metal catalyst and the like.

[0020] From the viewpoint of obtaining excellent radical resistance, the viscosity of solution A constituting the radical resistance improver at 23°C is preferably 40 Pa·s or more and 1200 Pa·s or less, more preferably 50 Pa·s or more and 500 Pa·s or less, and even more preferably 60 Pa·s or more and 200 Pa·s or less.

[0021] The content of the A solution constituting the radical resistance improver in the uncrosslinked rubber composition is preferably 7 parts by mass or more and 20 parts by mass or less, more preferably 10 parts by mass or more and 15 parts by mass or less, per 100 parts by mass of the hydrogen-containing fluororubber, from the viewpoint of obtaining excellent plasma resistance.

[0022] The uncrosslinked rubber composition may further contain a crosslinking aid. The crosslinking aid bonds to the hydrogen-containing fluororubber so as to be interposed between the hydrogen-containing fluororubber molecules when the hydrogen-containing fluororubber is crosslinked by a thermal crosslinking agent.

[0023] Examples of the crosslinking aid include triallyl cyanurate, trimethallyl isocyanurate, triallyl isocyanurate, triacryl formal, triallyl trimellitate, N,N'-m-phenylene bismaleimide, dipropargyl terephthalate, diallyl phthalate, tetraallyl terephthalate amide, triallyl phosphate, bismaleimide, fluorinated triallyl isocyanurate (1,3,5-tris(2,3,3-trifluoro-2-propenyl)-1,3,5-triazine). Examples of the crosslinking aid include tris(diallylamine)-S-triazine, triallyl phosphite, N,N-diallylacrylamide, 1,6-divinyldodecafluorohexane, hexaallyl phosphoramide, N,N,N',N'-tetraallylphthalamide, N,N,N',N'-tetraallylmalonamide, trivinyl isocyanurate, 2,4,6-trivinylmethyltrisiloxane, tri(5-norbornene-2-methylene)cyanurate, and triallyl phosphite. The crosslinking aid preferably contains one or more of these, and more preferably contains triallyl isocyanurate from the viewpoint of obtaining excellent plasma resistance.

[0024] In order to obtain excellent plasma resistance, the content of the crosslinking aid in the uncrosslinked rubber composition is preferably 1 part by mass or more and 10 parts by mass or less, more preferably 3 parts by mass or more and 5 parts by mass or less, per 100 parts by mass of the hydrogen-containing fluororubber.

[0025] The uncrosslinked rubber composition may contain polyvinylidene fluoride powder (PVDF powder) dispersed as a filler, since the problem of contamination inside the device due to the release of particles is unlikely to occur. The PVDF powder may be formed of either a homopolymer of vinylidene fluoride (VDF) or a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP), but the former is preferred from the viewpoint of obtaining excellent radical resistance.

[0026] From the viewpoint of obtaining excellent radical resistance, the volume average particle size of the PVDF powder is preferably 15 μm or less, more preferably 10 μm or less. From the same viewpoint, the melting point of the PVDF powder is preferably 165° C. or more and 172° C. or less. From the same viewpoint, the melt viscosity of the PVDF powder is preferably 35 kpoise or more and 39 kpoise or less. This melt viscosity is measured under the conditions of 232° C. and 100 seconds based on ASTM D3835.

[0027] In order to obtain excellent plasma resistance, the content of the PVDF powder in the uncrosslinked rubber composition is preferably 1 part by mass or more and 12 parts by mass or less, more preferably 3 parts by mass or more and 7 parts by mass or less, per 100 parts by mass of the hydrogen-containing fluororubber.

[0028] The uncrosslinked rubber composition may further contain rubber components other than the hydrogen-containing fluororubber, reinforcing materials such as carbon black, plasticizers, processing aids, vulcanization accelerators, antioxidants, surfactants, etc., so long as the application of the sealing material according to the embodiment is permitted.

[0029] The hardness of the crosslinked rubber composition forming the sealing material according to the embodiment is preferably 50 A or more and 70 A or less, more preferably 55 A or more and 65 A or less. This hardness is measured with a type A durometer based on JIS K6253-3:2012.

[0030] The tensile strength (TB) of the crosslinked rubber composition forming the sealing material according to the embodiment is preferably 13 MPa or more and 20 MPa or less, more preferably 14 MPa or more and 16 MPa or less. The elongation at break (EB) is preferably 150% or more and 400% or less, more preferably 250% or more and 350% or less. The 100% modulus (M 100 The tensile strength (TB), elongation at break (EB) and 100% modulus (M 100 ) is measured by a tensile test based on JIS K6251.

[0031] The compression set of the crosslinked rubber composition forming the sealing material according to the embodiment is preferably 15% to 50%, more preferably 25% to 35%, when the test time is 72 hours and the test temperature is 200° C., and is preferably 5% to 25%, more preferably 10% to 20%, when the test time is 72 hours and the test temperature is 150° C. These compression sets are measured based on JIS K6262:2013.

[0032] Next, a method for producing the sealing material according to the embodiment will be described.

[0033] In producing the sealing material according to the embodiment, first, an uncrosslinked rubber composition is prepared by kneading using an open type rubber kneader such as an open roll or an enclosed type rubber kneader such as a kneader.

[0034] Thereafter, a predetermined amount of the uncrosslinked rubber composition is filled into the cavity of a preheated mold, the mold is closed, and in this state, the mold is maintained at a predetermined molding temperature and a predetermined molding pressure for a predetermined molding time. In this way, the uncrosslinked rubber composition is molded into an uncrosslinked molded body having a shape of a seal material for the cavity, and the uncrosslinked molded body having a shape of a seal material is heated to crosslink the hydrogen-containing fluororubber with a thermal crosslinking agent. This molding may be press molding or injection molding. The molding temperature is, for example, 150°C or higher and 180°C or lower. The molding pressure is, for example, 0.1 MPa or higher and 25 MPa or lower. The molding time is, for example, 3 minutes or higher and 20 minutes or lower.

[0035] Then, the mold is opened and the sealing material according to the embodiment is removed from the inside.

[0036] The sealing material according to the embodiment of the molded article released from the mold may be irradiated with radiation to perform post-crosslinking. In this case, examples of the radiation include α-rays, β-rays, γ-rays, electron beams, ions, etc. Among these, the radiation is preferably electron beams or γ-rays. The radiation dose is preferably 20 kGy or more and 100 kGy or less. However, from the viewpoint of obtaining excellent heat aging resistance, it is preferable not to perform this radiation irradiation treatment on the molded article obtained by heating the uncrosslinked molded body to crosslink the hydrogen-containing fluororubber with a thermal crosslinking agent. EXAMPLES

[0037] (Crosslinked Rubber Composition) The crosslinked rubber compositions of the following Examples and Comparative Examples were prepared. The configurations of each are also shown in Table 1.

[0038] <Example 1-1> The mixture was mixed with 100 parts by mass of hydrogen-containing fluororubber FKM (Technoflon P959, Solvay), 1.5 parts by mass of thermal crosslinking agent peroxide (Perhexa 25B, Nippon Oil & Fats Co., Ltd., 2,5-dimethyl-2,5-di(t-butylperoxy)hexane), 12 parts by mass of two-component material 1 (SIFEL3405A / B, Shin-Etsu Chemical Co., Ltd.) having A component containing compound X and B component containing compound X and a crosslinking agent, which does not contain a crosslinking agent A component (silica content: 8.3% by mass, viscosity (23°C): 70 Pa·s), 4 parts by mass of crosslinking assistant triallyl isocyanurate (TAIC, Mitsubishi Chemical Co., Ltd.), and PVDF powder (Kynar MG15) as a filler. An uncrosslinked rubber composition was prepared by adding 5 parts by mass of Arkema (volume average particle size: 7.9 μm, melting point: 165 to 172° C., melt viscosity: 35 kpoise to 39 kpoise) and 0.5 parts by mass of a surfactant and kneading them. The uncrosslinked rubber composition was heated to crosslink the hydrogen-containing fluororubber FKM with the thermal crosslinking agent peroxide, to obtain a crosslinked rubber composition designated as Example 1-1.

[0039] <Example 1-2> The crosslinked rubber composition of Example 1-1 was irradiated with 30 kGy of gamma rays to obtain Example 1-2.

[0040] <Comparative Examples 1-1 and 1-2> The crosslinked rubber compositions obtained in the same manner as in Examples 1-1 and 1-2, except that liquid B containing a crosslinking agent (silica content: 10.6 mass%, viscosity (23°C): 80 Pa s) was used instead of liquid A of the two-component material 1, were designated as Comparative Examples 1-1 and 1-2, respectively.

[0041] <Comparative Examples 1-3 and 1-4> The crosslinked rubber compositions obtained in the same manner as in Examples 1-1 and 1-2, except that half of the A liquid in the two-component material 1 was replaced with B liquid and both A liquid and B liquid were used, were designated as Comparative Examples 1-3 and 1-4, respectively.

[0042] <Examples 2-1 and 2-2> The crosslinked rubber compositions obtained in the same manner as in Examples 1-1 and 1-2, except that the A component of the two-component material 1 was replaced with the A component (SIFEL3705A / B manufactured by Shin-Etsu Chemical Co., Ltd.) not containing a crosslinking agent (silica content: 21.8 mass%, viscosity (23°C): 1100 Pa s), were designated as Examples 2-1 and 2-2, respectively.

[0043] <Reference Examples 1 and 2> The crosslinked rubber compositions obtained in the same manner as in Examples 1-1 and 1-2, except that a one-component material (X-71-369, manufactured by Shin-Etsu Chemical Co., Ltd., silica content: 10 mass%, viscosity (23°C): 9 Pa s) was used instead of the A component of the two-component material 1, were designated as Reference Examples 1 and 2, respectively.

[0044] [Table 1]

[0045] (Test Method) <Hardness> For each of the Examples, Comparative Examples, and Reference Examples, the hardness was measured using a type A durometer based on JIS K6253-3:2012.

[0046] <Tensile properties> For each of the Examples, Comparative Examples, and Reference Examples, a tensile test was carried out based on JIS K6251, and the tensile strength (TB), elongation at break (EB), and 100% modulus (M 100 ) was measured.

[0047] <Compression set> For each of the Examples, Comparative Examples, and Reference Examples, the compression set (CS) was measured based on JIS K6262:2013 for a test time of 72 hours at a test temperature of 200°C, and for a test time of 72 hours at a test temperature of 150°C.

[0048] <Plasma resistance> For each of the examples, comparative examples, and reference examples, O2 plasma was irradiated using a microwave plasma generator. O2 and CF4 were used as reaction gases, and the flow rate ratio between them was 50:1. The reaction pressure was 100 Pa and the plasma irradiation time was 60 minutes. Then, the time from the start of plasma irradiation to the start of crack generation was measured. The mass loss rate after irradiating O2 plasma for 60 minutes was also calculated.

[0049] (Test Results) The test results are shown in Table 2.

[0050] [Table 2]

[0051] According to Table 2, Examples 1-1 and 1-2, which used only the A liquid of the two-component material 1, had a longer time from the start of plasma irradiation to the onset of cracks compared to the corresponding Comparative Examples 1-1 and 1-2, which used only the B liquid, and Comparative Examples 1-3 and 1-4, which used both the A liquid and the B liquid, and therefore had superior plasma resistance.

[0052] It can be seen that Examples 1-1 and 1-2, in which only the liquid A of the two-component material 1 was used, have superior plasma resistance compared to Examples 2-1 and 2-2, in which only the liquid A of the two-component material 2 was used.

[0053] It is clear that Example 1-1, which was not irradiated with gamma rays, has a smaller compression set and is therefore more excellent in heat aging resistance than Example 1-2, which was irradiated with gamma rays. [Industrial Applicability]

[0054] The present invention is useful in the technical field of sealing materials and manufacturing methods thereof.

Claims

1. A sealing material formed of a crosslinked rubber composition obtained by crosslinking an uncrosslinked rubber composition containing a hydrogen-containing fluororubber, a thermal crosslinking agent, and a radical resistance improver, The radical resistance improver is composed of only the A liquid of a two-component material having an A liquid containing a perfluoro skeleton compound having two or more alkenyl groups in its molecule and no crosslinking agent, and a B liquid containing a perfluoro skeleton compound having two or more alkenyl groups in its molecule and a crosslinking agent, and the uncrosslinked rubber composition is a sealing material to which only the A liquid of the two-component material is added, and no B liquid is added.

2. The sealing material according to claim 1, The sealing material, wherein the content of silica in the liquid A is 25 mass % or less.

3. The sealing material according to claim 1, The sealing material, wherein the viscosity of the liquid A at 23° C. is 40 Pa·s or more and 1200 Pa·s or less.

4. The sealing material according to claim 1, The sealing material, wherein the content of the solution A in the uncrosslinked rubber composition is 7 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the hydrogen-containing fluororubber.

5. The sealing material according to claim 1, The sealing material comprises the uncrosslinked rubber composition containing polyvinylidene fluoride powder dispersed therein.

6. The sealing material according to claim 5, The sealing material, wherein the content of the polyvinylidene fluoride powder in the uncrosslinked rubber composition is 1 part by mass or more and 12 parts by mass or less per 100 parts by mass of the hydrogen-containing fluororubber.

7. The sealing material according to claim 1, The crosslinked rubber composition has a tensile strength of 13 MPa or more as measured in accordance with JIS K6251.

8. The sealing material according to claim 1, The crosslinked rubber composition has a compression set of 35% or less, as measured based on JIS K6262:2013 at a test time of 72 hours and a test temperature of 200°C.

9. A method for producing a sealing material according to any one of claims 1 to 8, comprising the steps of: A method for producing a sealing material, comprising the steps of: preparing an uncrosslinked rubber composition containing the hydrogen-containing fluororubber, the thermal crosslinking agent, and the radical resistance improver; molding the uncrosslinked rubber composition into an uncrosslinked molded article having a shape of a sealing material; and heating the uncrosslinked molded article to crosslink the hydrogen-containing fluororubber with the thermal crosslinking agent, thereby obtaining a molded article.

10. The method for producing a sealing material according to claim 9, The method for producing a sealing material does not involve irradiating the molded product obtained by heating the uncrosslinked molded body to crosslink the hydrogen-containing fluororubber with the thermal crosslinking agent.

Citation Information

Patent Citations

  • Rubber product and manufacturing method therefor

    JP2019052226A

  • Rubber product and method for producing the same

    JP2019214743A

  • Rubber article and production method of the same, and rubber product

    JP2020203444A

  • Rubber molding

    JP2022097403A